An intersectional analysis of sociodemographic disparities in Covid-19 vaccination: A nationwide register-based study in Sweden - Spetz, M.; Lundberg, L.; Nwaru, C.; Li, H.; Santosa, A.; Ng, N.; Leach, S.; Gisslén, M.; Hammar, N.; Nyberg, F.; Rosvall, M. (Vaccine, 2022)
Studies on sociodemographic disparities in Covid-19 vaccination uptake in the general population are still limited and mostly focused on older adults. This study examined sociodemographic differences in Covid-19 vaccination uptake in the total Swedish population aged 18–64 years. National Swedish register data within the SCIFI-PEARL project were used to cross-sectionally investigate sociodemographic differences in Covid-19 vaccination among Swedish adults aged 18–64 years (n = 5,987,189) by 12 October 2021. Using logistic regression models, analyses were adjusted for sociodemographic factors, region of residence, history of Covid-19, and comorbidities. An intersectional analysis approach including several cross-classified subgroups was used to further address the complexity of sociodemographic disparities in vaccination uptake. By 12 October 2021, 76·0% of the Swedish population 18–64 years old had received at least two doses of Covid-19 vaccine, an additional 5·5% had received only one dose, and 18·5% were non-vaccinated. Non-vaccinated individuals were, compared to vaccinated, more often younger, male, had a lower income, were not gainfully employed, and/or were born outside Sweden. The social patterning for vaccine dose two was similar, but weaker, than for dose one. After multivariable adjustments, findings remained but were attenuated indicating the need to consider different sociodemographic factors simultaneously. The intersectional analysis showed a large variation in vaccine uptake ranging from 32% to 96% in cross-classified subgroups, reflecting considerable sociodemographic heterogeneity in vaccination coverage. Our study, addressing the entire Swedish population aged 18–64 years, showed broad sociodemographic disparities in Covid-19 vaccine uptake but also wide heterogeneities in coverage. The intersectional analysis approach indicates that focusing on specific sociodemographic factors in isolation and group average risks without considering the heterogeneity within such groups will risk missing the full variability of vaccine coverage. SciLifeLab / Knut & Alice Wallenberg Foundation, Swedish Research Council, Swedish government ALF agreement, FORMAS.